Kesiapan UMKM di Kabupaten Sambas dalam Menghadapi Implementasi Coretax - Susiana, Utie; Mukaromah, Lailatul; Luthfi, Muhammad Farisan; Sentiya, Novi (Indonesian Accounting Literacy Journal, 2025)
The government has actively pursued reforms in the tax sector,, including introducing Coretax. Coretax system or core system of tax service administration, for registration, administration, payment and reporting into one. Coretax was issued by the government in (PMK) Number 81 of 2024 concerning Tax Provisions in the context of the Implementation of the Core System of Tax Administration (Coretax). This study aims to determine the readiness of MSMEs in Sambas Regency in facing the implementation of coretax. This study uses qualitative research methods. Data was obtained through interviews, documentation and observation. The focus of the interview questions refers to Parasuraman developing the Technology Readiness Index (TRI), namely Optimism, Discomfort, Innovativeness, and Insecurity. The results of the study show that the readiness of MSMEs in Sambas Regency in facing coretax shows a positive response to digital transformation, but still faces complex dynamics.